(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Sports have become a popular and effective way to achieve developmental goals due to theirwidespread appeal. PE programs often incorporate sport-specific instruction, which helps students growphysically, emotionally, socially, and morally. Sports and competitive games are essential for socialadvancement and gaining admiration from peers. Playing a sport involves engaging in physical activitywith the goal of winning, improving performance, or having fun. Different types of sports have uniquemethods and abilities required by each team. Cultivating the capacity to play with excellent skill andconsistently perform well is crucial for fitness and sports. General athletic ability and motor ability areinterchangeable, with motor abilities such as power, speed, agility, balance, and reaction time beingessential for players. In developed countries, there is a strong emphasis on motor learning or skilldevelopment among children, leading to higher levels of general fitness. Physiological factors, such asvital capacity and blood pressure, can influence both the volleyball player and the game. Every volleyballteam needs to monitor each player’s physiological profile, while mental health measures like anxietylevels can impact their performance. Physical fitness measures, such as explosive strength, endurance,and agility, also impact volleyball players and the game itself. This research aims to analyze volleyballplayers’ skills based on anthropometric, and physical variable. The study will focus on 25 volleyballplayers from Gondia, Maharashtra, who compete at the intercollegiate level.